A Simple Experimental Model to Investigate Force Range for Membrane Nanotube Formation - Lor, Chai; Lopes, Joseph D.; Mattson-Hoss, Michelle K.; Xu, Jing; Hirst, Linda S. (Frontiers in Materials, 2016)
The presence of membrane tubules in living cells is essential to many biological processes. In cells, one mechanism to form nanosized lipid tubules is via molecular motor induced bilayer extraction. In this paper, we describe a simple experimental model to investigate the forces required for lipid tube formation using kinesin motors anchored to 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) vesicles. Previous related studies have used molecular motors actively pulling on the membrane to extract a nanotube. Here, we invert the system geometry; molecular motors are used as static anchors linking DOPC vesicles to a two-dimensional microtubule network and an external flow is introduced to generate nanotubes facilitated by the drag force. We found that a drag force of ≈7 pN was sufficient for tubule extraction for vesicles ranging from 1 to 2 μm in radius. By our method, we found that the force generated by a single molecular motor was sufficient for membrane tubule extraction from a spherical lipid vesicle.